2020
DOI: 10.1186/s40694-020-00101-4
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of hyphal pellet formation mediated by polysaccharides, α-1,3-glucan and galactosaminogalactan, in Aspergillus species

Abstract: Filamentous fungi are widely used for production of enzymes and chemicals, and are industrially cultivated both in liquid and solid cultures. Submerged culture is often used as liquid culture for filamentous fungi. In submerged culture, filamentous fungi show diverse macromorphology such as hyphal pellets and dispersed hyphae depending on culture conditions and genetic backgrounds of fungal strains. Although the macromorphology greatly affects the productivity of submerged cultures, the specific cellular compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 101 publications
(183 reference statements)
1
26
0
Order By: Relevance
“…The morphology is influenced by different cultivation parameters including the temperature, pH value, medium composition, inoculum concentration or mechanical stress [ 17 ]. A pellet morphology is advantageous regarding the flow behavior of the culture broth, resulting in a Newtonian flow accompanied by a lower viscosity compared to media containing dispersed mycelia [ 18 ]. However, the oxygen and nutrient supply is limited within biomass pellets which can lead to cell lysis in the pellet core.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology is influenced by different cultivation parameters including the temperature, pH value, medium composition, inoculum concentration or mechanical stress [ 17 ]. A pellet morphology is advantageous regarding the flow behavior of the culture broth, resulting in a Newtonian flow accompanied by a lower viscosity compared to media containing dispersed mycelia [ 18 ]. However, the oxygen and nutrient supply is limited within biomass pellets which can lead to cell lysis in the pellet core.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-wall polysaccharides are thought to be synthesized on the plasma membrane after the secretory vesicles containing polysaccharide synthases have been exported to the hyphal tip (Riquelme, 2013). On the basis of our previous findings (Miyazawa et al, 2020), we hypothesize the process of alkali-soluble glucan biosynthesis of A. nidulans to be as follows:…”
Section: Discussionmentioning
confidence: 85%
“…fumigatus , A. nidulans agsB and its orthologues are clustered with two α-amylase-encoding genes ( amyD and amyG in A . nidulans ) (He et al, 2014;Yoshimi et al, 2017;Miyazawa et al, 2020). The amyG gene encodes an intracellular α-amylase and is crucial for α-1,3-glucan synthesis (He et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Formation of mycelium pellets is one of the hurdles that can negatively affect the fermentation efficacy of industrial fungi for biomaterial productions [ 20 , 55 ]. It was previously considered that fungal mycelium pellets was formed by the winding of hyphae to form aggregated and compact pellets [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the bacterium EPS Pel [16], GAG can also mediate biofilm formation to increase the resistance of A. fumigatus against antifungal drugs [17,18]. In addition, it has been found that the cell wall GAG as well as α-1,3-glucan can mediate the aggregation of A. oryzae hyphae to form mycelium pellets in liquid culture [19,20]. Production of the EPSs containing α-1,4 linked GalNAc and GalN has also been reported in a few non-Aspergillus ascomycete fungi such as Neurospora crassa, Penicillium frequentans and Paecilomyces sp.…”
Section: Introductionmentioning
confidence: 99%